Bridge‐to‐surgery stent placement versus emergency surgery for acute malignant colonic obstruction. Issue 7 (16th April 2014) - van den Berg, M. W.; Sloothaak, D. A. M.; Dijkgraaf, M. G. W.; van der Zaag, E. S.; Bemelman, W. A.; Tanis, P. J.; Bosker, R. J. I.; Fockens, P.; ter Borg, F.; van Hooft, J. E.
<x xml:space="preserve">Abstract</x> Background Endoscopic self‐expanding metal stent (SEMS) placement as a bridge to surgery is an option for acute malignant colonic obstruction. There is ongoing debate regarding the superiority and oncological safety of SEMS placement compared with emergency surgery. This retrospective study aimed to compare outcomes of these treatment approaches. Methods Patients were identified from cohorts treated between 2005 and 2012 in two teaching hospitals, of which one used emergency surgery only in patients with large bowel obstruction, whereas the other attempted SEMS placement. Only patients treated with curative intent were included. Results The study included 59 patients in whom SEMS placement was attempted and 51 who underwent surgery alone. The successful primary anastomosis rate was higher in the SEMS group than in the surgery‐alone group among patients with left‐sided obstruction (30 of 43 versus 10 of 34 respectively; P = 0·001), whereas stoma formation was less common (11 of 43 versus 23 of 34; P < 0·001). Such differences were not apparent in patients with right‐sided obstruction. Secondary stoma rates were comparable between treatment approaches (left‐sided: 11 of 43 versus 13 of 34, P = 0·322; right‐sided: 1 of 16 versus 1 of 17, P = 1·000). There were no significant differences in morbidity, mortality, recurrence or survival. Conclusion Endoscopic SEMS placement increased the primary anastomosis rate in patients with left‐sided large bowel obstruction.